PEMBENTUKAN KATA BENDA DALAM BAHASA JERMAN (THE NOUN FORMATION OF GERMAN) - Donna Retty M. Timbuleng (Kadera Bahasa, 2016)
This scientific study of this paper is entitled “Formation of Nouns in German” . The problem that is studied are What are the elements of the establishment of German nouns and how the process of formation of German nouns. To analyze the elements of the establishment of German Nouns and formation, the theory used is the theory of Bunting and Naumann.The purpose of this paper is to identify the elements forming nouns German and classification, analysis and description of noun-forming process. The method uses the descriptive method with data collection library